2022
DOI: 10.3232/gcg.2021.v15.n3.02
|View full text |Cite
|
Sign up to set email alerts
|

Motivators for the Use of Vehicle Sharing Services on Demand in Brazil

Abstract: El estudio se centró en determinar los motivadores para el uso de medios de transporte bajo demanda en Brasil. Los procedimientos metodológicos involucraron el Análisis Factorial Exploratorio para validar las variables y el Análisis FactorialConfirmatorio estableció el modelo ajustado y las dimensiones en las que estos elementos aparecían en la percepción de los usuarios. Se puede observar que los motivadores fueron relevantes, sin embargo, solo tres variables de carácter utilitario están fuertemente ligadas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…e a qualidade e disponibilidade do transporte público, principalmente durante a pandemia por Covid-19. Outros prognósticos são as tarifas reduzidas, a disponiblidade tecnólogica 13 e a expectativa de benefícios 14 (Violin, 2021). A Figura 6 ilustra a relação entre número de emplacamentos de carros e os períodos com e sem Uber no mercado brasileiro.…”
Section: Resultados Dos Modelos Estimadosunclassified
“…e a qualidade e disponibilidade do transporte público, principalmente durante a pandemia por Covid-19. Outros prognósticos são as tarifas reduzidas, a disponiblidade tecnólogica 13 e a expectativa de benefícios 14 (Violin, 2021). A Figura 6 ilustra a relação entre número de emplacamentos de carros e os períodos com e sem Uber no mercado brasileiro.…”
Section: Resultados Dos Modelos Estimadosunclassified
“…Great attention is given to the drivers of adoption, with a rich branch of research aimed at identifying the motives behind the consideration or use of sharing economy services. Scholars within this sub-topic largely agree on considering the economic benefits that might arise from the sharing economy as one of the key drivers, regardless of the sector (Wu et al, 2017;Ek Styv en and Mariani, 2020;Jain and Mishra, 2020;Tsai et al, 2021;Violin, 2021). However, the economic motivation is also integrated with non-economic drivers such as social relations (Lee and Wong, 2021;Say et al, 2021), social projection (Jain and Mishra, 2020), enjoyment (Tsai et al, 2021) Great attention is also given to risk perception and trust, a further sub-topic emerging from this cluster.…”
Section: Sharing Approachmentioning
confidence: 99%
“…It is observed that the need for agile displacements and with lower barriers of time and place of boarding provided by the ride (Violin, 2021b) can be an important inducer of use. Considering the multiplicity of variables, Table 2 was created, which presents international studies related to the topic: Improved supply conditions can be an attraction element.…”
Section: Women and Ride-hailingmentioning
confidence: 99%